Desarrollo y ejecución de un taller sobre cultura turística dirigido a niños de escasos recursos de la cooperativa la karolina, parroquia Pascuales, cantón Guayaquil - Betancourt Medranda, Jenny (2009)
The current paper is based on a tourism culturalization program whose objective is to make children of low-income families be aware of the importance of tourism as well as to strengthen their identity as Ecuadorians. In order to develop this program, a poll was done to find out the level of knowledge of children between 11 and 12 years old living in Cooperativa La Karolina, a peripheral zone of Guayaquil. 69% of these children demonstrated a low level of knowledge on basic touristic information about Ecuador. According to these results, the content of a program of touristic culture was created, resulting in 4 workshops. In order to evaluate the results obtained through the workshops, each child was given a mark using evaluation criteria and considering the time of participation. The execution of these workshops and its results show a significant influence of a touristic culture program on the perception of children about tourism. In addition, these workshops made children participants aware of their importance as citizens and how their actions are fundamental to the development of their community. As professionals in Tourism, we have chosen the subject of this thesis to contribute to the tourism development of Ecuador with the expectation that children whom participated in the tourism culture workshops will be very soon the new tourism managers in any place of Ecuador where they would reside.